2020
DOI: 10.1113/ep088468
|View full text |Cite
|
Sign up to set email alerts
|

Older adults show elevated intermuscular coherence in eyes‐open standing but only young adults increase coherence in response to closing the eyes

Abstract: Understanding neural control of standing balance is important to identify age-related degeneration and design interventions to maintain function. Here, intermuscular coherence between antagonist muscle pairs around the ankle-joint during standing balance tasks was investigated before and after strength training. Ten young (18-31 years; YOUNG) and nine older adults (66-73 years; OLDER) stood on a force plate for 120 s with eyes open followed by 120 s with eyes closed before and after 14 weeks of strength traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…We observed a significant increase in IMC across all frequency ranges during the unstable compared to the stable condition. These effects are in line with previous studies that also observed increased IMC during tasks which challenge postural control e.g., standing position (e.g., tandem stance) or through inducing threats (e.g., standing at height; Boonstra et al, 2015;Danna-Dos-Santos et al, 2015;Walker et al, 2020). These findings indicate that IMC was reliably estimated in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a significant increase in IMC across all frequency ranges during the unstable compared to the stable condition. These effects are in line with previous studies that also observed increased IMC during tasks which challenge postural control e.g., standing position (e.g., tandem stance) or through inducing threats (e.g., standing at height; Boonstra et al, 2015;Danna-Dos-Santos et al, 2015;Walker et al, 2020). These findings indicate that IMC was reliably estimated in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the difficulty in channeling the correct standing balance and the related neuromuscular activities varies depending on the available sensory inputs (Carver et al, 2006;Jeka et al, 2010). For example, more significant postural sway and specific neuromuscular activity while standing with eyes closed than with eyes open (Danna-Dos-Santos et al, 2015;Walker et al, 2020) has been reported. In addition, elderly adults (Nojima et al, 2018;Fujio and Takeuchi, 2021) and patients with stroke (de Haart et al, 2004) have a greater loss of standing balance in response to sensory disturbances than healthy young adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neuromuscular system must significantly assist this process by actively modulating it to an appropriate level [ 2 ]. Successful integration of vestibular and somatosensory systems is required for optimal balance control, but age negatively affects the functioning of these systems [ 3 ]. An analysis that may help to explain this phenomenon is a simple calculation of the coherence of a pair of antagonistic muscles (tibialis anterior muscle and soleus muscle), which are relevant in investigating neuromuscular mechanisms controlling the ankle joint.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis that may help to explain this phenomenon is a simple calculation of the coherence of a pair of antagonistic muscles (tibialis anterior muscle and soleus muscle), which are relevant in investigating neuromuscular mechanisms controlling the ankle joint. The relationships that exist between the muscles mentioned above have already been analyzed by a number of authors [ 2 , 3 , 4 ]. However, due to the complexity of the ankle joint stability problem, further exploration of this topic is still needed, if only due to the increase in life expectancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation